MORPHOFUNCTIONAL ALTERATIONS OF THE ESOPHAGUS INDUCED BY CARBON MONOXIDE EXPOSURE AND POTENTIAL APPROACHES FOR THEIR CORRECTION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
To investigate structural and immunohistochemical alterations in the esophagus caused by prolonged carbon monoxide (CO) exposure and to assess the therapeutic potential of phytocompounds derived from Silybum marianum (milk thistle) and Carthamus tinctorius (safflower)